Implementasi Penatausahaan Hasil Hutan Hak di Kabupaten Polewali Mandar Sulawesi Barat - Andi Arafat; Yusran Yusran; Mas'ud Junus; Adrayanti Sabar (Fakultas Kehutanan, Universitas Hasanuddin, 2017)
Position forest rights as one of the supporting timber availability in the industry can not be separated from the challenges and dynamics of forest product administration. It required a review of management of forest products from the forest rights in its implementation. This study aims to analyze the implementation of the rights of forest product administration in Polewali Mandar, using descriptive analysis with the existing indicators on variables and dimensions were obtained in accordance with the guidelines for the interview. The results of analysis tools provide the opportunity regulatory administration of forest products to the widest public / private forest owners as well as the adjustment of government policy related to the field of forestry sustainable forest management (SFM) and Timber Legality Verification (VLK). Implementation of the regulatory activities in the form of socialization only held one and the absence of formal socialization to the new set of rules; Issuing Certificates of Origin (SKAU) wood as much as 33 (thirty-three) of 144 (one hundred and forty-four) villages, yet the publisher SKAU set by BP2HP; SKAU publishing process by following the same line district offices are not in line with existing regulations and create problems in terms of time, cost and control; The lack of reporting of forest production and recapitulation SKAU Publisher SKAU to the district forestry department reporting that impact the realization of the production and distribution of forest products are not going well right. Implementation of the management of forest products in Polewali Mandar rights do not go according to Forestry Minister Regulation No. P.30 / Menhut-II / 2012 are rearranged in the Minister of Environment and Forestry No. P.21 / MenLHK-II / 2015 on the administration of forest products of forest rights